Agglomeration tendency and activated carbon concentration effects on activated carbon‐polysulfone mixed matrix membrane performance: A design of experiment formulation study. Issue 37 (29th July 2022) - Lewis, Jeremy; Alshami, Ali; Talukder, Musabbir; Owoade, Ademola; Baker, Kelsey; Onaizi, Sagheer
Abstract: Mixed matrix membranes (MMMs) are effective materials for emerging separation applications. While MMMs show promise, various membrane formation schemes have produced particle agglomerations, surface ruptures, and varying separation performance as a result. In this work, a replicated 2 × 2 3 full factorial design of experiment (DOE) and a mixture analysis was conducted to investigate the effects of activated carbon, polyethylene glycol (PEG), and solvent type, used during MMM formation. Aniline blue filtration was used as a model for performance. A thorough analysis was conducted on contact angle, agglomeration frequency, water flux, and dye rejection. Specifically, a novel and facile method to study agglomeration tendencies is presented. Among other trends, agglomeration tendencies were mitigated by the addition of PEG during the fabrication process. Water flux increased from 10 to 55 LMH when PEG was used as a pore former and dye rejection increased from 72% to 90% with the addition of AC particles. Abstract : DOE formulation study on activated carbon‐polysulfone mixed matrix membranes.